3D printed biodegradable functional temperature-stimuli shape memory polymer for customized scaffoldings. (August 2020) - Pandey, Akash; Singh, Gurminder; Singh, Sunpreet; Jha, Kanishak; Prakash, Chander
Abstract: Shape memory polymers (SMPs) and their composites have become the prominent choice of the various industries owing to the unique inherent characteristics which can be stimulated through the exposure of external stimuli. The use of SMPs in the three-dimensional (3D) technologies has produced enormous advantages. However, the potential of SMPs in 3D printing has limitedly explored. In the present study, an investigation was performed to study the shape memory effect (SME) of the fused filament fabricated (FFF) chitosan (CS) reinforced poly-lactic-acid (PLA) based porous scaffolds. Firstly, the composite filaments, with 1, 1.5, and 2% wt. of CS, were fabricated by using the twin-screw extrusion process, which was later used to print the test specimens at different infill density. The printed samples were selectively pre-elongated to 2.5 mm and then processed through direct heating, at 60-70 °C, for enabling the SME. It has been observed that the CS particles acted as rigid phases and interrupted the re-ordering of PLA chain. However, the scaffoldings showed 18.8% shape recovery at optimized process parametric settings. In addition, wettability and biocompatibility analyses of developed scaffoldings have also been performed to investigate the biological aspects of the developed scaffoldings. The stimulated samples found to be possessed with good wettability and cell proliferation. Overall, the 3D printed PLA/CS porous scaffoldings have shown significant shape recovery characteristics and are biologically active to be used as self-healing implants for acute bone deficiencies. Graphical abstract: Image 1 Highlights: Investigated the shape memory characteristics of 3D printed PLA/CS scaffolds. Described the effect of heat-stimuli on wetability and biocompatibility. Outlined the scope of developing scaffoldings.